Pemanfaatan Pangan Lokal Dalam Program Breastfeeding Nutrition Empowerment Untuk Meningkatkan Keberhasilan ASI Eksklusif - Sri Heryani; Hani Septani; Mela Mustikasari (Jurnal Obstretika Scientia, 2026)
Exclusive breastfeeding is an important strategy to improve infant health status and prevent stunting. However, the coverage of exclusive breastfeeding in Indonesia has not yet reached the national target due to low breast milk production, limited maternal knowledge regarding breastfeeding nutrition, and the underutilization of local food as a nutritional source for lactation. This study aimed to analyze the effect of local food utilization in the Breastfeeding Nutrition Empowerment program on the success of exclusive breastfeeding. The study employed a quasi-experimental design using a pretest-posttest with control group design. A total of 60 breastfeeding mothers participated and were divided into intervention and control groups using purposive sampling techniques. The intervention included breastfeeding nutrition education, local food processing training, and breastfeeding assistance. Research instruments consisted of a knowledge questionnaire, the Breastfeeding Self-Efficacy Scale (BSES), and breast milk production observation sheets. The results showed a significant increase in maternal knowledge, breastfeeding self-efficacy, breast milk production, and exclusive breastfeeding success in the intervention group with a p-value < 0.05. The utilization of local food in the Breastfeeding Nutrition Empowerment program was proven effective in supporting exclusive breastfeeding success and can be developed as a community empowerment strategy based on local wisdom.